Assessment of Phagocytic Activity of Leukoconcentrate Neutrophils Cryopreserved with Dimethyl Acetamide after Post-Thaw Rehabilitation in Medium Containing Cord Blood Low-Molecular Fraction (Below 5 kDa) - Gulevsky, A. K.; Akhatova, Yu. S.; Moiseeva, N. N.; Gorina, O. L.; Chizhevsky, V. V.; Stepanyuk, L. V. (Problems of Cryobiology and Cryomedicine, 2024)
The influence of the cattle cord blood low-molecular fraction (below 5 kDa) on the functional activity of leukocytes after cryopreservation was studied. The stimulating effects of the fraction (0.15 mg/ml) on digesting and engulfing activities of frozenthawed neutrophils were observed. It was established that the usage of dimethyl acetamide (5%) as a cryoprotectant allowed preserving up to 80% of viable leukocytes.